2019
DOI: 10.1190/geo2018-0124.1
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the depth of investigation in the magnetotelluric method from the phase

Abstract: Proper computation for depth of investigation (DOI) of the magnetotelluric (MT) method is vital because the standard approximate depth transforms provide the depth corresponds to the interpreted conductivities instead of the actual DOI of MT. Previous works on DOI estimation of the MT method are based on 1D inversion. Although the previous works are significant, the methods of DOI calculation are lengthy and affected by non-uniqueness of inverse modeling. Therefore, to overcome these problems, we developed a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Data quality for most stations is good, although a few MT sites near densely populated area suffer from high cultural noise, especially in TNCO and ENCC, which were excluded in the 3-D inversion. We applied the latest formula (Borah & Patro, 2019) to estimate the depth-of-investigation (DOI) for the used data before 3-D inversion, and the results showed that the DOIs of BBMT and LMT data are almost greater than 60 and 150 km, respectively (Figure S1 in Supporting Information S1).…”
Section: Magnetotelluric Data and 3-d Inversionmentioning
confidence: 99%
“…Data quality for most stations is good, although a few MT sites near densely populated area suffer from high cultural noise, especially in TNCO and ENCC, which were excluded in the 3-D inversion. We applied the latest formula (Borah & Patro, 2019) to estimate the depth-of-investigation (DOI) for the used data before 3-D inversion, and the results showed that the DOIs of BBMT and LMT data are almost greater than 60 and 150 km, respectively (Figure S1 in Supporting Information S1).…”
Section: Magnetotelluric Data and 3-d Inversionmentioning
confidence: 99%